Relationship between resilience and self‐care in people with chronic conditions: A systematic review and meta‐analysis. Issue 9 (22nd February 2022) - Jin, Yuanyuan; Bhattarai, Muna; Kuo, Wan‐chin; Bratzke, Lisa C.
Abstract: Background: Living with chronic condition(s) is difficult, due in part to the complexities of effective disease self‐care. Self‐care has been considered a challenging process according to the literature which describes multiple barriers patients with chronic conditions experience. Resilience has the potential to buffer the adversities of daily self‐care and maintain physical and emotional well‐being. No systematic review and meta‐analysis have been conducted to synthesise and quantify the relationship between resilience and self‐care across chronic conditions. Aims: (1) To examine how the definitions and measurements of self‐care and resilience align with the middle‐range theory of self‐care of chronic illness (i.e. self‐care maintenance, self‐care monitoring, and self‐care management) and 3 Rs of resilience process from the society‐to‐cells framework (i.e. resistance, recovery and rebound) across different chronic conditions; and (2) to examine whether and the degree to which resilience is correlated with self‐care across different chronic conditions. Design: Systematic review and meta‐analysis, following PRISMA guidelines. Methods: PubMed, CINAHL, SocINDEX and PsychINFO were searched for quantitative studies published from January 2000 through July 2020. Descriptive data were summarised using numerical counting to provide an overview of the study characteristics. Definitions and measurements of self‐care and resilience were synthesised narratively based on self‐care and resilience theories. Numerical data with Pearson's product–moment correlation among observational studies were examined using meta‐analysis. Results: This review included 20 articles, involving 9, 269 individuals across 11 chronic conditions. Despite self‐care and resilience being defined and operationalised in a variety of ways, most definitions shared some underlying core constructs. Meta‐analysis showed a positive relationship between resilience and self‐care across chronic conditions. Findings from interventional studies indicated a bidirectional relationship between resilience and self‐care. Conclusions: Overall, resilience was positively associated with self‐care in people with chronic conditions. Longitudinal and experimental studies are needed to better understand the causal relationship between resilience and self‐care. Relevant to clinical practice: Resilience has the potential to buffer the adversities of daily self‐care and maintain physical and emotional well‐being. The positive relationship between resilience and self‐care found in this review provides preliminary evidence for clinicians to not only focus on reducing barriers and risk factors of self‐care but also to improve or increase patients' resilience through various evidence‐based interventions.